Effect of gamma irradiation on plant regeneration from cotyledon explants of tomato (solanumlycopersicon) - P. KARUNAKAR RAO (International Journal of Pharma and Bio Sciences, 2018)
Tomato is a major vegetable crop that has achieved tremendous popularity over the last century. It is grown in almost every country of the world. Ionization of plant cells causes disruption of the normal processes of the cell growth ultimately effecting crop yield. Gamma ray’s are dose dependent, where the low dose has fewer side effects in contrast to a high dose that effects plant phenotype, including various cell organelles and Biochemical components. However there are several biochemical parameters to identify the damage caused by this radiation. The present investigations were undertaken to study the effect of gamma irradiation on cotyledons obtained from irradiated seeds. Callusing ability and number of shoots were used as parameters to study the effect of irradiation. Attempts were also made to determine the optimal dose of the mutagen that induce highest number of shoots per explant. The seeds of solanumlycopersicon cv Pusa Ruby were soaked for 24 hours and treated with 10 KR, 20 KR, 30 KR, 40 KR, 50 KR and 60 KR of gamma irradiation. The mutagenized cotyledon explants were cultured on MS medium supplemented with IAA, NAA and BAP to study the mutagenic effect on morphogenesis and shoot formation. A comparative study was made to assay suitable dose of irradiation to the Control seeds. The results indicated that the fresh and dry weight of callus gradually increased in lower doses and decreased with the increase of dose of irradiation. The maximum mean number of shoots were recorded at 30 KR and number of shoots were decreased at 40 KR and explants did not respond at higher doses of 50 KR & 60 KR treated seeds. Callus induction was inhibited at higher doses and the callus production and weight were found to be dose dependent. However, the present investigations lower doses of gamma-irradiation were stimulatory in producing more number of shoots.